Cholinergic activation suppresses palmitate-induced macrophage activation and improves acylation stimulating protein resistance in co-cultured adipocytes. Issue 9 (May 2017) - Wu, Jing; Jiao, Zhou-yang; Li, Rui-zhen; Lu, Hui-ling; Zhang, Hao-hao; Cianflone, Katherine
Acylation-stimulating protein (ASP), produced through activation of the alternative complement immune system, modulates lipid metabolism. Using a trans-well co-culture cell model, the mitigating role of α7-nicotinic acetylcholine receptor (α7nAChR)-mediated cholinergic pathway on ASP resistance was evaluated. ASP signaling in adipocytes via its receptor C5L2 and signaling intermediates Gαq, Gβ, phosphorylated protein kinase C-α, and protein kinase C-ζ were markedly suppressed in the presence of TNFα or medium from palmitate-treated RAW264.7 macrophages, indicating ASP resistance. There was no direct effect of α7nAChR activation in 3T3-L1 cell culture. However, α7nAChR activation almost completely reversed the ASP resistance in adipocytes co-cultured with palmitate-treated RAW264.7 macrophages. Further, α7nAChR activation could suppress the production of pro-inflammatory molecules TNFα and interleukin-6 produced from palmitate-treated co-cultured macrophages. These results suggest that macrophages play a significant role in the pathogenesis of ASP resistance and α7nAChR activation secondarily improves adipose ASP resistance through suppression of inflammation in macrophages. Impact statement: 1. Adipocyte–macrophage interaction in acylation-stimulating protein (ASP) resistance 2. Lipotoxicity induced inflammatory response in ASP resistance 3. A vicious circle between lipotoxicity and inflammatory response in ASP resistance 4. Cholinergic modulation of inflammatory response in adipocyte and macrophage